2012
DOI: 10.1021/la204831b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Structure of Poly(dopamine)

Abstract: Herein we propose a new structure for poly(dopamine), a synthetic eumelanin that has found broad utility as an antifouling agent. Commercially available 3-hydroxytyramine hydrochloride (dopamine HCl) was polymerized under aerobic, aqueous conditions using tris(hydroxymethyl)aminomethane (TRIS) as a basic polymerization initiator, affording a darkly colored powder product upon isolation. The polymer was analyzed using a variety of solid state spectroscopic and crystallographic techniques. Collectively, the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
749
3
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 965 publications
(815 citation statements)
references
References 89 publications
40
749
3
8
Order By: Relevance
“…Early studies showed that the presence of 3,4-dihydroxy-L-phenylalanine (DOPA) and lysine-rich proteins were responsible for the extremely robust adhesion of mussels 3,[5][6][7][8] . In 2007, Lee et al reported the first publication using dopamine (DA), with a similar molecular structure of DOPA, to obtain an adhesive pDA film 5,7,9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that the presence of 3,4-dihydroxy-L-phenylalanine (DOPA) and lysine-rich proteins were responsible for the extremely robust adhesion of mussels 3,[5][6][7][8] . In 2007, Lee et al reported the first publication using dopamine (DA), with a similar molecular structure of DOPA, to obtain an adhesive pDA film 5,7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Lee et al reported the first publication using dopamine (DA), with a similar molecular structure of DOPA, to obtain an adhesive pDA film 5,7,9 . Later on new pDA properties as well as interesting applications in biosensors, sensors, remediation, biomineralization, drug delivery and hyperthermia have been reported 3,[6][7][8][9][10][11][12][13][14][15] . The very reactive residual quinone groups in pDA allow further derivatizations with nitrogen and thiol residues through Schiff base formation or Michael-type addition respectively 3,6,7,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…FT-IR spectrum of PDA (24 h polymerized) powder shows absorption bands of indoline, indole, carbonyl, amino and hydroxyl groups of PDA which is also in accordance with previous reports (see Supporting Information for more information, Figure S3 and Table S1). [ 36,37 ] Note that exact chemical structure (it is assumed that PDA is composed of covalently linked dihydroxyindole, indoledione, and dopamine units) or microstructure (e.g. linear polymers, cylclic oligomers, physical aggregates or combinations of these structures) of PDA is still not fully resolved; [ 38 ] therefore we cannot conclusively determine the exact structure of the synthesized polymer in our experimental conditions.…”
Section: Fabrication Of Textured Fibersmentioning
confidence: 98%
“…[ 35,36 ] UV-Vis absorption spectra of the 24 h polymerized DA solution shows the typical broad band absorption of PDA (Supporting Information, Figure S2a). [ 37 ] The transmission of PEI fi lm signifi cantly reduced after coating with PDA (24 h) due to the broad band light absorption of PDA (Supporting Information, Figure S2b). FT-IR spectrum of PDA (24 h polymerized) powder shows absorption bands of indoline, indole, carbonyl, amino and hydroxyl groups of PDA which is also in accordance with previous reports (see Supporting Information for more information, Figure S3 and Table S1).…”
Section: Fabrication Of Textured Fibersmentioning
confidence: 99%
“…The absence of any covalent binding has been proposed, and that PDA solely consists of monomers held together by strong noncovalent forces including charge transfer, -stacking and hydrogen bonding. 15 Also, a model has been proposed where it was suggested that PDA is formed through two di®er-ent pathways occurring in parallel: (1) the noncovalent self-assembly of stable complexes of (DA) 2/5,6-dihydroxyindole (DHI) and (2) covalent polymerization. 13 Furthermore, the coexistence of structurally di®erent components (un-cyclized catecholamine/quinones, cyclized DHI units and pyrrolecarboxylic acid moieties) within PDA that can be a®ected by the dopamine concentration has been demonstrated.…”
Section: Instructionmentioning
confidence: 99%